THE ROLE OF EU INNOVATION POLICIES IN THE SUSTAINABLE DEVELOPMENT OF THE ENERGY SECTOR - SIRBU, Olesea; CRUDU, Rodica; IGNATOV, Augustin (Studia Universitatis Babeș-Bolyai Oeconomica, 2017)
https://doi.org/10.1515/subboec-2017-0006 In the present conditions when the demographic pressure upon the environment is higher than ever, the humanity faces the challenge of sustainability. Namely the sustainability of human activities is important and nothing can assure it better than sustainable energy supplies. The European Union is the leading global power in terms of adjusting its policies to increase innovation to assure a sustainable growth of its energy sector as a key to an advanced economic system. The present research focuses on the impact of European Union policies on the sustainable development of its energy sector by analyzing quantitatively and qualitatively various indicators intended to offer a throughout insight. The results obtained focus on the identification of the main innovation paradigms; the description of the main modern environmental challenges, especially in the energy domain; the determination of the relation between innovation and energy sustainability, and its analysis at the level of European Union. JEL classification: H50, Q20, Q40, Q50;